Mitigation of Acute Hepatotoxicity Induced by Cadmium Through Morin: Modulation of Oxidative and Pro-apoptotic Endoplasmic Reticulum Stress and Inflammatory Responses in Rats - Sengul, Emin; Yildirim, Serkan; Cinar, İrfan; Tekin, Samet; Dag, Yusuf; Bolat, Merve; Gok, Melahat; Warda, Mohamad (Springer Science and Business Media LLC, 2024)
AbstractCadmium (Cd) is a toxic heavy metal with significant environmental health hazards. It enters the body through various routes with tissue accumulation. The relatively longer half-life with slow body clearance significantly results in hepatotoxicity during its liver detoxification. Therefore, researchers are exploring the potential use of herbal-derived phytocomponents to mitigate their toxicity. Here, we investigated, for the first time, the possible ameliorative effect of the phytochemical Morin (3,5,7,29,49-pentahydroxyflavone) against acute Cd-induced hepatotoxicity while resolving its underlying cellular mechanisms in a rat animal model. The study involved 50 adult male Sprague–Dawley rats weighing 200–250 g. The animals were divided into five equal groups: control, Cd, Morin100 + Cd, Morin200 + Cd, and Morin200. The 2nd, 3rd, and 4th groups were intraperitoneally treated with Cd (6.5 mg/kg), while the 3rd, 4th, and 5th groups were orally treated with Morin (100 and 200 mg/kg) for 5 consecutive days. On the 6th day, hepatic function (serum ALT, AST, ALP, LDH enzyme activities, and total bilirubin level) testing, transcriptome analysis, and immunohistochemistry were performed to elucidate the ameliorative effect of Morin on hepatotoxicity. In addition to restoring liver function and tissue injury, Morin alleviated Cd-induced hepatic oxidative/endoplasmic reticulum stress in a dose-dependent manner, as revealed by upregulating the expression of antioxidants (SOD, GSH, Gpx, CAT, and Nrf2) and decreasing the expression of ER stress markers. The expression of the proinflammatory mediators (TNF-α, IL-1-β, and IL-6) was also downregulated while improving the anti-inflammatory (IL-10 and IL-4) expression levels. Morin further slowed the apoptotic cascades by deregulating the expression of pro-apoptotic Bax and Caspase 12 markers concomitant with an increase in anti-apoptotic Blc2 mRNA expression. Furthermore, Morin restored Cd-induced tissue damage and markedly suppressed the cytoplasmic expression of JNK and p-PERK immunostained proteins. This study demonstrated the dose-dependent antioxidant hepatoprotective effect of Morin against acute hepatic Cd intoxication. This effect is likely linked with the modulation of upstream p-GRP78/PERK/ATF6 pro-apoptotic oxidative/ER stress and the downstream JNK/BAX/caspase 12 apoptotic signaling pathways.
Keywords: Male; Research; Body Weight; Apoptosis; Hepatitis, Animal; Endoplasmic Reticulum Stress; Flavones; Antioxidants; Rats; Rats, Sprague-Dawley; Oxidative Stress; Animals; Chemical and Drug Induced Liver Injury; Cadmium